2021
DOI: 10.1002/pssa.202100417
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Annealing Temperature before Cooling under Magnetic Field on Perpendicular Exchange Coupling in (Pt/Co)5/NiO

Abstract: The effects of the annealing temperature before cooling under a magnetic field on the perpendicular exchange coupling in Pt/Co multilayers directly coupled to a NiO layer are studied in the NiO layer thickness range of 1–4 nm. The obtained results reveal that the exchange bias (EB) field and the magnetization reversal process depend on the NiO layer thickness as well as on the annealing temperature. Positive EB fields are observed, especially for 4 nm‐thick NiO layer. However, the values obtained here are low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…However, in some cases of FM/AFM coupling a positive shift was also observed. [ 24 ] This can partly explain our results. Gredig et al reported a temperature dependence EB in these samples.…”
Section: Resultsmentioning
confidence: 55%
“…However, in some cases of FM/AFM coupling a positive shift was also observed. [ 24 ] This can partly explain our results. Gredig et al reported a temperature dependence EB in these samples.…”
Section: Resultsmentioning
confidence: 55%